2023
DOI: 10.3389/fimmu.2023.1125260
|View full text |Cite
|
Sign up to set email alerts
|

Development of severe colitis is associated with lung inflammation and pathology

Abstract: Inflammatory bowel diseases (IBD) such as Crohn’s disease and ulcerative colitis are chronic relapsing diseases that affect the gastrointestinal tract, most commonly the colon. A link between the gut and the lung is suggested since patients with IBD have an increased susceptibility for chronic inflammatory lung disease. Furthermore, in the absence of overt lung disease, IBD patients have worsened lung function and more leukocytes in sputum than healthy individuals, highlighting a conduit between the gut and lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…The incidence of pneumonia lesions on CT images was significantly higher in the PE group (36.9%) compared to the DVT group (26.3%) ( p < 0.0001) (Table 2). Previous studies have suggested that chronic lung disease, chronic digestive disease, trauma, and tumors could induce pulmonary inflammation 22–25 . In our study, only connective tissue disease, trauma, and surgery exhibited significantly higher incidence rates in the DVT group compared to the PE group.…”
Section: Resultssupporting
confidence: 42%
See 1 more Smart Citation
“…The incidence of pneumonia lesions on CT images was significantly higher in the PE group (36.9%) compared to the DVT group (26.3%) ( p < 0.0001) (Table 2). Previous studies have suggested that chronic lung disease, chronic digestive disease, trauma, and tumors could induce pulmonary inflammation 22–25 . In our study, only connective tissue disease, trauma, and surgery exhibited significantly higher incidence rates in the DVT group compared to the PE group.…”
Section: Resultssupporting
confidence: 42%
“…Previous studies have suggested that chronic lung disease, chronic digestive disease, trauma, and tumors could induce pulmonary inflammation. [22][23][24][25] In our study, only connective tissue disease, trauma, and surgery exhibited significantly higher incidence rates in the DVT group compared to the PE group. Nevertheless, this difference does not provide an explanation for the higher rate of pneumonia lesions observed in the PE group, which could potentially be attributed to PE.…”
Section: Comparison Of Pneumonia Lesion Incidence Between the Pe And ...mentioning
confidence: 93%
“…For lung samples, serial 4 μm-thick sections of the left lung were collected. Another subset of mice were euthanised by rapid decapitation following sodium pentobarbitone overdose, for collection of bronchoalveolar lavage fluid (BALF) via in situ lung lavage [ 45 ]. Mice were then decapitated, and the brains extracted from the skull.…”
Section: Methodsmentioning
confidence: 99%
“…Digital lung slides were viewed with Aperio ImageScope v.12.4.3 at 10x magnification. Alveolar airspace size was quantified using the mean linear intercept (MLI) method [ 45 , 49 ]. Briefly, 20 equal length lines were drawn over images of H&E-stained lung cross-sections, then the number of intercepts with alveolar walls were counted.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, this dual impact may play a role in initiating or exacerbating susceptibility to COPD. There are indications that patients with inflammatory bowel disease (IBD) have an increased susceptibility to pulmonary manifestations ( 2 ), and animal studies have suggested that intestinal and systemic inflammation in colitis models would predispose these patients to lung pathologies ( 3 , 4 ). Moreover, a disturbed gut microbiota was observed after cigarette smoke and particulate matter exposure ( 5 7 ).…”
mentioning
confidence: 99%